Personal Affairs in E. M. Foster's A Passage to India Passage , Personal, India: الشؤون الشخصية في ممر إي إم فورستر إلى الهند (مجلة ديالى للبحوث الانسانية, 2022)
"A Passage to India" is the most excellent novel written by the English author, Edward Morgan Forster. It deals with misunderstandings which arise in  relationships among humans beings. The novel is based on Forster's experiences in India. The whole novel is an expedition made by three English individuals, Mr. Fielding, Miss Adela, Mrs. Moore. They try to see India for what it is.  This paper attempts to shed light on the theme of personal affairs of individuals who come from two different cultures and religions by following the characters analysis approach.